Arnobius Iunior, Praedestinatus - Arnobius Iunior ca. 5. Jh; Iulianus Aeclanensis 380-455 (Brepols, 2022)
For the first time in English, the 'Praedestinatus' represents a moment in the fifteen-century old theological conversation in Latin Christianity about the topics of grace, predestination and free will. Written as a response to Augustine's growing theological influence, this book should not merely be regarded as a work of apologetics, despite the author's intention, but seen as breaking controversial new ground because of his claim that a small circle of heretics was acting as a ?fifth column? within the Church, undermining orthodox beliefs concerning God, his providence and all-inclusive love. The translator's introduction sheds light on the authorship, dating and historical context of this work. It documents how this text was received and critically assessed for a period of over the twelve centuries: from the time of Augustine in the fifth century to that of the bitter Jansenist controversy in the seventeenth. It entered those latter debates shortly after its rediscovery by Jacques Sirmond in the library of the Reims cathedral in a manuscript that, in the ninth century, was in the possession of Hincmar ? the archbishop of Reims who in his time had revived disputes about grace and free will. Sirmond named the text ?[the] Praedestinatus? when he published its first edition in 1643.00After a three hundred year hiatus, interest in the 'Praedestinatus' revived in the twentieth century thanks to German and French scholars who studied the book?s theological trajectory and claims. Its critical edition was eventually accomplished in 2000 by Italian scholar Franco Gori. The present translation is based on Gori's edition.
Als möglicher Verfasser von "Praedestinatus" gilt auch Julianus von Eclanum
Keywords: Geschichte 450; Semipelagianismus; Prädestination; Gnadenlehre; Quelle